We can define a field F with the following properties:

  • Binary operations + (addition) and ⋅ (multiplication)
  • Commutativity
  • Associativity
  • Identities
  • Inverses
  • Distributivity

Now, the additive inverse existence condition can be equivalently replaced with the statement ∀a∈F 0a=0, because each one is a consequence of the other.

The proof (assuming 0=0a): $$0=0a=(1-1)a=a+(-1a)$$ Which means that for every a there exists an additive inverse, more precisely it is -1a.

But now take the set {0,1} with logical conjunction for ⋅; and inclusive disjunction for +. (so that 1+1=1)

  • 1 doesn't have an additive inverse, as 1+1=1+0=1≠0
  • concurrently, 0⋅0=0 and 0⋅1=0; so this indeed appears to be a field by the alternative condition.

Which is a contradiction.


The error is in my proof that 0=0a →-1a=-a, because -1∉{0,1}.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.